Transfer Modality Research Initiative - Bangladesh (TMRI) - Ahmed, Akhter; Hoddinott, John F.; Roy, Shalini (International Food Policy Research Institute, 2012)
This is a randomized control trial in two zones of Bangladesh (north and south). Treatment is assigned at the village level where treatments are: cash transfers (north and south); cash transfers + nutrition behavior communication change (north only); food transfers (north and south); food transfers + nutrition behavior communication change (south only); food-cash split (north and south); and controls (north and south). Within treatment localities, women living in very poor households are targeted to receive benefits for two years.